HPMC K15M and Carbopol 940 mediated fabrication of ondansetron hydrochloride intranasal mucoadhesive microspheres - Poonam Dhawale, Nilesh M. Mahajan, Debarshi Kar Mahapatra, Ujwala N. Mahajan, Purushottam S. Gangane (Journal of Applied Pharmaceutical Science, 2018)
The purpose of the present research was the design, development, and evaluation of ondansetron hydrochloride loaded polymeric mucoadhesive microspheres for intranasal delivery to avoid first-pass metabolism phenomenon in the liver and to improve its residence time. The microspheres were fabricated by a solvent evaporation method using carbopol 940 and HPMC K15M as a mucoadhesive polymer along with ethyl cellulose as a film-forming polymer. The intention of the current study was to comprehensively examine the influence of formulation components and the probable process variables such as a polymer to polymer ratio and stirring rate on the characteristics of the microspheres prepared. The microspheres were characterized for drug-polymer interactions, entrapment efficiency, drug loading, swelling property, particle size analysis, thermal behavior, morphological, in-vitro mucoadhesion, ex-vivo drug permeation, in-vitro drug release, histopathology, and release kinetic studies. The research will open new avenues for increasing the bioavailability of ondansetron hydrochloride in the future.
Keywords: Nasal drug delivery,Mucoadhesive,Microsphere, Solventevaporation technique,Ondansetron hydrochloride,Bioavailability.